Boost your vocabulary - Phillips, Sam. (New Delhi : Goodwill Publishing House)
here is no denying the fact that words are a great power. You can possess full command of a language only if you have strong command of its vocabulary. English is no exception! If you want to hone your English skills, you must boost your English vocabulary. The present book, Boost Your Vocabulary, created to make learning of English words a real fun and pleasure through several strategies and exercises, is a means of instant word power and understanding. It is so organised as to make one more fluent, confident and harmonious when it comes to expressing oneself.